Hubungan Pola Asuh Orangtua dan Fatigue dengan Prokrastinasi Akademik Peserta Didik - Rahmanisa, Rendi Yana; Marjohan, Marjohan; Netrawati, Netrawati; Sukma, Dina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe parenting styles, describe fatigue, describe academic procrastination and examine the relationship between parenting styles and fatigue with academic procrastination. This type of research is quantitative research using descriptive and correlational analysis approaches. In this study, what was described was parenting parents, fatigue and academic procrastination of students. The population in this study were students of class VIII MTsS Al-Hidayah Pasaman Barat, totaling 182 students. The number of samples in this study were 125 students who were taken using a proportional stratified random sampling technique. This study used two data analysis techniques, namely descriptive analysis and correlational analysis. Descriptive analysis was carried out using the percentage formula while correlational analysis used the product moment correlation formula and the calculation was assisted by using the SPSS version 20.0 for windows program. The results showed (1) the level of parenting in general was in the low category, (2) the level of fatigue was generally in the high category, (3) the level of academic procrastination of MtsS Al-Hidayah Pasaman Barat students was generally in the high category and (4) there is a significant relationship between parenting and fatigue with academic procrastination of MTsS Al-Hidayah Pasaman Barat students with a correlation coefficient of 0.704 and a significance level of 0.000. In conclusion, there is a significant relationship between parenting and fatigue with academic procrastination of students at MTsS Al-Hidayah Pasaman Barat. The implications of the research results can be used as input for creating a guidance and counseling service program at MTsS Al-Hidayah Pasaman Barat. Keywords: Parenting Style, Fatigue, Academic Procrastination